Guidance for Research on Social Isolation, Loneliness, and Participation Among Older People: Lessons From a Mixed Methods Study. Issue 1 (3rd September 2019) - Dare, Julie; Wilkinson, Celia; Donovan, Robert; Lo, Johnny; McDermott, Marie-Louise; O'Sullivan, Helen; Marquis, Ruth
This article provides methodological guidance to researchers wishing to develop collaborative research projects with local governments and other agencies, by describing the process adopted in a mixed methods study conducted in the City of Wanneroo (the City), a local government area in Perth, Western Australia. The study explored factors related to older people's (60+ years) participation in community-based activities and links between their participation and levels of social isolation, loneliness, and social connectedness. The research incorporated four interrelated stages: (1) an audit of existing programs in the City and program participant characteristics; (2) focus groups with program participants and interviews with nonparticipants; (3) a cross-sectional survey to assess factors associated with participation and links to social isolation, loneliness, and social connectedness; (4) face-to-face interviews with survey respondents screened at risk for loneliness. Methodological recommendations are provided to guide future collaborative research with local authorities, program developers, and administrators, aimed at minimizing social isolation and loneliness among older people. These include the need for clear communication and documentation of mutually agreed research objectives and responsibilities from project initiation to completion, identifying and working with local agencies to maximize recruitment among "hard to reach" groups, understanding the dimensions of loneliness addressed in the selected instrument used to screen for loneliness, and integrating innovative data collection techniques when working with vulnerable groups such as socially isolated older people.